NF-κB Inhibitory Activity of the Di-Hydroxy Derivative of Piperlongumine (PL-18) - Yael Schlichter Kadosh; Subramani Muthuraman; Ariel Kushmaro; Rajendran Saravana Kumar; Jacob Gopas (Journal of Immunology Research)
Inflammation is a critical response of the immune system to infection or injury, serving to repair and restore tissue homeostasis. While acute inflammation generally protects against harmful stimuli, prolonged and chronic inflammation have detrimental effects and disrupts tissue homeostasis. Due to the complex and multifactorial etiology of chronic inflammation, effective treatment remains elusive. We found that piperlongumine (PL)-18, a di-hydroxy derivative of PL from long pepper, inhibits the nuclear factor kappa B (NF-kB), a master transcription factor of numerous components of the inflammatory response. NF-kB was inhibited by PL-18 in two human cell-lines, L428 and A549, by preventing the nuclear translocation of p65 NF-kB. We also found that IκB kinase (IKK) was degraded in the presence of PL-18. Furthermore, PL-18 inhibited the production of proinflammatory cytokines expressed by L428, a cell line with a constitutive active NF-kB. Altogether, our results suggest that PL-18 is a molecule of interest to be further developed to treat persistent infections with severe inflammation.